1989
DOI: 10.1073/pnas.86.15.5834
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in membrane protein band 3 associated with accelerated erythrocyte aging.

Abstract: We report a human band 3 alteration that is associated with anemia as determined by a reticulocyte count of 20%. Erythrocyte defects included increased IgG binding, increased breakdown products of band 3, and altered anionand glucose-transport activity in middle-aged cells. These changes were observed during normal erythrocyte aging in situ. Binding of ankyrin to band 3 was normal. Serum/cell crossover studies indicated that a neoantigen appears on the propositus' erythrocytes to which IgG from both propositus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 24 publications
(19 reference statements)
2
50
0
Order By: Relevance
“…Others have estimated that, at 37°C, 25-35% of band 3 molecules rotate with correlation times < 150 ,us, 30-50% rotate with correlation times -3 ms, and 25-35% are rotationally immobile on the time scale ofthe experiment (67,69). Recent measurements with improved instrumentation indicate that about one-half of the rapidly rotating fraction of band 3 molecules rotate with correlation times of 25 to 30 As (67) (81,82), abnormally exposed galactosyl residues (46,83,84), and clustered band 3 molecules (27,48,50). Our data support the hypothesis that band 3 aggregation provides an important surface marker for RBC removal from the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Others have estimated that, at 37°C, 25-35% of band 3 molecules rotate with correlation times < 150 ,us, 30-50% rotate with correlation times -3 ms, and 25-35% are rotationally immobile on the time scale ofthe experiment (67,69). Recent measurements with improved instrumentation indicate that about one-half of the rapidly rotating fraction of band 3 molecules rotate with correlation times of 25 to 30 As (67) (81,82), abnormally exposed galactosyl residues (46,83,84), and clustered band 3 molecules (27,48,50). Our data support the hypothesis that band 3 aggregation provides an important surface marker for RBC removal from the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides were analyzed on 6-25% or 12-25% linear gels (6,7,(27)(28)(29). Immunoautoradiography was performed by immunoblotting as described (6,7,(28)(29)(30). Immunoblots were exposed to Kodak Ortho G (OG-1) film at -700C by our standard procedures (29,30).…”
Section: Methodsmentioning
confidence: 99%
“…Senescent cell antigen (SCA), an aging antigen, is a protein that appears on old cells and acts as a specific signal for the termination of that cell by initiating the binding of IgG autoantibody and subsequent removal by phagocytes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). SCA occurs on all cells examined (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because release of band 3 from its ankyrin and adducin linkages to the cytoskeleton can facilitate changes in multiple membrane properties, the authors suggested that tyrosine phosphorylation of band 3 may produce changes in erythrocyte biology that allow the cell to respond to initial stress (Ferru et al, 2011). Another marker of red blood cell apoptosis is band 3 clustering, which generates a cell surface epitope identified by autologous IgG antibodies and may act as a signal for the removal of erythrocytes from circulation (Kay et al, 1989). The nitration of tyrosine residues in proteins occurs through the action of reactive oxygen and nitrogen species such as peroxynitrite, the product of the reaction between nitric oxide and superoxide anion.…”
Section: Wwwintechopencom Anemia 28mentioning
confidence: 99%